(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
INACAP receives students of different ages and backgrounds, which generates a high diversity in the classroom. The differences in the skills and prior knowledge required for each subject are amplified, discouraging less-advantaged students and impacting their performance, passing, and dropping rates. A systematic work could be positive in the teaching-learning process, especially in complex subjects. This work presents the experience and results with a methodology of peer tutors with a chemistry subject. In each tutoring, the tutors were students with different styles and levels of learning to motivate the complement and feedback of the group work. The students developed autonomy and became aware of their learning process, which positively influenced it. They received academic support to encourage generic competencies such as self-management, teamwork, and problem-solving. The results showed a high student satisfaction rate (84.4%) and a considerable increase in performance in the Mineral Chemistry subject: a 50% increase in the averages and a 25% decrease in failure. The project team is convinced that it is feasible to implement this innovation in other subjects.